Secondhand smoke exposure and ocular health: a systematic review - Zhang, Youjuan; Zhang, Xiu Juan; Yuan, Nan; Wang, Yumeng; Ip, Patrick; Chen, Li Jia; Tham, Clement C.; Pang, Chi Pui; Yam, Jason C. (Survey of ophthalmology, 2023)
The toxicology of secondhand smoke (SHS), along with the harm of its exposure to human health, has been generally acknowledged; however, specific evidence is lacking on the association between SHS exposure and ocular health. In this systematic review (PROSPERO registration number: CRD42022247992), we included 55 original articles published by 12 May 2023, which dealt with SHS exposure and ocular disorders, such as eye irritation, conjunctivitis, dry eye diseases, uveitis, myopia, astigmatism, contact lens discomfort, age-related macular degeneration, glaucoma, and thyroid eye disease that addressed the ocular neurovascular structures of the macular, retinal nerve fiber layer, choroid, and corneal biomechanical parameters. We found compelling correlational evidence for eye irritation, conjunctivitis, and dry eye symptoms—supporting that SHS exposure was positively associated with inflammatory and allergic changes in the eyes. Yet, evidence about the associations between SHS exposure and other ocular disorders, structures, and parameters is still limited or controversial. Given the limitations of existing literature, more investigations with high quality and rigorous design are warranted to elucidate the potentially harmful effects of SHS exposure on ocular health.